The Responsibility of Coastal States Against the Ship Crash in International Strait (Malacca Strait) - Femmy Asdiana; Chomariyah; Wisnu Aryo Dewanto (Hang Tuah Law Journal, 2018)
Malacca Strait is globally recognized as a strait for international shipping as mentioned in UNCLOS 1982 and is under the sovereignty of three states; Indonesia, Malaysia, and Singapore. Seeing the position of Malacca Strait that becomes the most crowded lane of international trade and oil, it often raises problems in navigation. In addition, many rocks, corals and strong waves may increase the potential of ship wrecking, sinking, and crashes. In regard to the safety issue of shipping lane in Malacca Strait, it becomes the responsibility of the coastal states and thus, they should organize an integrated safety management among them, particularly in Malacca Strait. They are Indonesia, Malaysia, and Singapore. The safety assurance of shipping in Malacca Strait may increase the global economy as international oil trading and distribution is wellconducted, and finally it may increase the economy of the coastal states in Malacca Strait.